An annotated catalogue of nonditrysian Lepidoptera of India - Das, Apurva; Singh, Navneet (Zootaxa, 2022)
The present catalogue comprises 88 species in 24 genera and 10 families of nonditrysian Lepidoptera from India. Information on type localities, records from India including their diversity in different biogeographic zones of India and from outside India is included. Among all, Hepialidae is the dominant family, consisting 25 species in four genera whereas, the least dominant families are Palaeosetidae and Incurvariidae with one species each. Biogeographically, North-East is home to maximum species (37 in eight families) of primitive Lepidoptera, followed by Himalaya (31 species in five families), Western Ghats (24 species in seven families) with Hepialidae as a dominating family in all the three zones. No nonditrysian is reported from Desert and Islands. Among the states of India, Meghalaya is the most diverse with 27 species in seven families.